2023
DOI: 10.1186/s12885-023-11216-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 control on lung, breast, and colorectal pathological cancer diagnoses. A comparison between the Netherlands, Aotearoa New Zealand, and Northern Ireland

Abstract: Background The COVID-19 pandemic was managed in Aotearoa New Zealand (NZ) by a COVID-19 elimination policy, involving border closure and an initial national lockdown. This was different to most other countries including Northern Ireland (NI) and the Netherlands (NED). We quantify the effect of these policies on the diagnosis of three major cancers, comparing NZ with these two European countries. Method Data from NED, NZ and NI population-based canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…7,8 A recent study found reduced lung, breast and colorectal pathology-confirmed cancers in Northern Ireland and the Netherlands compared to Aotearoa/New Zealand, which reflect differences in disruptions to screening and healthcare services, patient presentations to primary and secondary care and wider societal restrictions. 21 While studies have examined parts of the cancer patient pathway, we are not aware of a population-based study which examines the impact of the COVID-19 pandemic on the entire cancer patient pathway, from presentation to diagnosis through to treatment and finally to survival. Our study utilises pre-pandemic and inter-pandemic data to describe changes in finalised cancer registrations in Northern Ireland, to assess changes by demographic (age, sex) and socioeconomic (deprivation) characteristics, to investigate differences in mode of presentation, basis of diagnosis and stage distribution at diagnosis, to examine changes in treatments received and differences in overall and net survival 1-year following diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 A recent study found reduced lung, breast and colorectal pathology-confirmed cancers in Northern Ireland and the Netherlands compared to Aotearoa/New Zealand, which reflect differences in disruptions to screening and healthcare services, patient presentations to primary and secondary care and wider societal restrictions. 21 While studies have examined parts of the cancer patient pathway, we are not aware of a population-based study which examines the impact of the COVID-19 pandemic on the entire cancer patient pathway, from presentation to diagnosis through to treatment and finally to survival. Our study utilises pre-pandemic and inter-pandemic data to describe changes in finalised cancer registrations in Northern Ireland, to assess changes by demographic (age, sex) and socioeconomic (deprivation) characteristics, to investigate differences in mode of presentation, basis of diagnosis and stage distribution at diagnosis, to examine changes in treatments received and differences in overall and net survival 1-year following diagnosis.…”
Section: Introductionmentioning
confidence: 99%